Pocket Money - Roderick Hunt (USA Oxford University Press, 2001)
The 'Stage 8 Biff, Chip and Kipper stories' provide a rich story context to help develop language comprehension and decoding skills. Stories and More Stories continue to provide a mix of fantasy settings and familiar situations. More complex sentences develop stamina, to enable readers to progress with confidence.
Keywords: Independent Reading -- Independent Reading